Differences in sensory characteristics among various mango cultivars in the form of fresh sliced mango, mango purée, and mango sorbet - Ledeker, Christie N. (Kansas State University, 2011)
Fresh mangoes are highly perishable, and therefore, they are often processed to extend shelf-life and facilitate exportation. Studying the transformation that mango cultivars undergo throughout processing can aid in selecting appropriate varieties for products. In the 1st part of this study, the flavor and texture properties of 4 mango cultivars available in the United States (U.S.) were analyzed. Highly trained descriptive panelists in the U.S. evaluated fresh, purée, and sorbet samples prepared from each cultivar. Purées were made by pulverizing mango flesh, passing it through a china cap, and heating it to 85 °C for 15 s. For the sorbets, purées were diluted with water (1:1), sucrose was added, and the bases were frozen in a batch ice cream freezer. Much of the texture variation among cultivars was lost after fresh samples were transformed into purées, whereas much of the flavor and texture variation among cultivars was lost once fresh mangoes and mango purées were transformed into sorbets. Compared to the other cultivars, Haden and Tommy Atkins underwent greater transformations in flavor throughout sorbet preparation, and processing reduced the intensities of some unpleasant flavors in these cultivars. Tommy Atkins was the only cultivar that had flavor differences from other cultivars when it was in sorbet. Results suggest that cultivar variation is generally not detectable in mango sorbet unless the cultivar has a distinct initial flavor. In the 2nd part of this study, descriptive panelists in Thailand evaluated the flavor and texture properties of fresh samples and purées prepared from 6 cultivars grown in Thailand. Thermal processing had unique effects on the flavor of each cultivar, especially Nam Dok Mai and Chok Anun; Nam Dok Mai significantly decreased in mango identity and peach flavors after processing, whereas Chok Anun significantly increased in sweet, mango identity, and pineapple flavors. Although a slight amount of flavor variation among cultivars was lost because of thermal processing, most of the texture variation was eliminated. Because of significant changes in flavor and texture after heat treatment of mango cultivars, manufacturers should select cultivars for mango purées based on their properties after thermal processing.
Keywords: Sensory analysis; Mango cultivars; Descriptive analysis; Puree; Sorbet; Processing; Food Science (0359)